Inkling - Oppel, Kenneth, 1967-; Smith, Sydney, 1980- (2018)
When an inkblot, who can write, listen, learn, and draw, jumps out of Mr. Rylance's sketchbook, Ethan believes he may be the answer to their problems and names him Inkling.
"A Borzoi Book"--Title page verso.
8-12
Accelerated Reader AR
Keywords: Grief -- Juvenile fiction; Families -- Juvenile fiction; Artists -- Juvenile fiction; Grief -- Fiction; Family life -- Fiction; Artists -- Fiction; Artists -- Fiction; Family life -- Fiction; Grief -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Themes / Values & Virtues; JUVENILE FICTION / Books & Libraries; Artists; Families; Grief; JUVENILE FICTION / Humorous Stories; Graphic novels -- Fiction; Fiction; Juvenile works; Illustrated works